Faktor-Faktor yang Berhubungan dengan Implementasi Promosi Kesehatan Rumah Sakit - Mufid, Achmad; Sulaeman, Lalu; Sastrawan, Sastrawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study analyzes factors (superior support, commitment, resources, and communication) related to implementing Hospital Health Promotion (PKRS). The method used is quantitative with a cross-sectional analytical approach. The research results showed that there was a relationship between superior support (p=0.001), commitment (p=0.027), resources (p=0.000), and communication (p=0.022) on the implementation of Hospital Health Promotion (PKRS). In conclusion, the better the support from superiors, commitment of implementers, resources, and communication, the better the implementation of PKRS. Keywords: Supervisor Support, Commitment, Resources, Communication, Health Promotion